THE ETHICS OF UTILIZING THE YOUTUBE PLATFORM IN THE PHENOMENON OF INFLUENCER'S LUXURY EXHIBITION (The Potential for Relative Deprivation by Digital Natives in Indonesia) - Al Azis, Muhammad Rachdian (UNIVERSITAS PAKUAN, 2021)
Advances in today's communication technology have allowed people to interact with each other with foreign cultures. So, in the process, it is not uncommon to find cases which are later found to be put into a category where ethics can be neglected at the regional level which is indirect [12]. The Youtube platform, which in the process, has in fact carried out the function of mass media, for example, by having a significant effect as the main supplier of information needs for the audience, will certainly really need creator content that can prioritize ethics. And, to take it further, users are also part of the industry. It becomes a problem when luxury exhibitions are made into content, because there is an element of social inheritance that the Youtube Platform has in terms of the function of mass communication. Where this condition can then be interpreted as the mass media also has a function as an educator by passing on ideas from figures or in other terms, namely transmitting culture. (Littlejohn, 2005) Is it true that luxury exhibitions are one of the topics of study that would be passed on to future generations? Considering that if you use the lens of relative deprivation—where relative deprivation is described as a situation that does not have a match between the realities of life experienced and the definition of a decent life, between expectations for a job and the life experienced [13]—then it becomes a new question. if the phenomenon of showing off luxury carried out by these influencers is then justified. Because vlogs on the youtube platform in the process are then considered to be one of the benchmarks in living life by digital natives who are filled by the younger generation. If the answer is that luxury exhibitions can increase the motivation of users or viewers to work harder, then know that not everyone has access to become rich and can play this luxury. The reason people at the top level work together to maintain the stratification system is that they benefit from the stratification system and the way in which rewards are distributed [23].